1980
DOI: 10.1021/bi00545a024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ternary complex formation between dihydrofolate reductase, coenzyme, and inhibitors

Abstract: The kinetics of ligand binding to dihydrofolate reductase from Lactobacillus casei (MTX/R) to form the ternary enzyme-inhibitor-coenzyme complex have been investigated by the stopped-flow fluorescence technique. The fluorescence changes observed when coenzymes or inhibitors bind to the binary complex of the enzyme with the complementary ligand occur in a single fast phase. Under pseudo-first-order conditions the reaction traces could be fitted with precision to a single-exponential decay, and apparent bimolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 13 publications
3
56
0
Order By: Relevance
“…Previously, the binding of MTX to E. coli DHFR was shown to decrease tryptophan fluorescence due to quenching of Trp 22 in ecDHFR (Appleman et al, 1988), and the same change in Trp fluorescence upon ligand binding has been observed by others (Dunn and King, 1980). In principal, binding at the substrate and the NADPH binding sites can be evaluated by fluorescence spectroscopy (Appleman et al, 1988).…”
Section: Resultssupporting
confidence: 59%
“…Previously, the binding of MTX to E. coli DHFR was shown to decrease tryptophan fluorescence due to quenching of Trp 22 in ecDHFR (Appleman et al, 1988), and the same change in Trp fluorescence upon ligand binding has been observed by others (Dunn and King, 1980). In principal, binding at the substrate and the NADPH binding sites can be evaluated by fluorescence spectroscopy (Appleman et al, 1988).…”
Section: Resultssupporting
confidence: 59%
“…TMP is a specific inhibitor of eDHFR with much lower affinity for mammalian DHFRs ( K d = 20 pM versus 4 μM for bacterial and mammalian DHFRs, respectively. Importantly, the interaction between eDHFR and TMP is noncovalent, though dissociation is very slow (T 1/2 ~20 minutes (Dunn and King, 1980)). TMP can be modified at the 4 position of the B ring with retention of potency and selectivity (Figure 2A; (Calloway et al, 2007)).…”
Section: Resultsmentioning
confidence: 99%
“…The rate constants for binding ligands to DHFR in either the cofactor or the substrate binding sites can be measured by following the quenching of the intrinsic enzyme fluorescence due predominantly to its tryptophan residues. In the formation of binary complexes of DHFR at saturating substrate concentration, two exponentials were observed, a rapid phase whose rate was dependent on ligand concentration followed by a ligand-independent phase, while in the formation of ternary complexes (by addition of a ligand to the binary complex) a single ligand-dependent exponential is observed (Dunn et al, 1978; 3.50 - Dunn & King, 1980;Cayley et al, 1981). Cayley et al (1981) concluded that this behavior is due to the mechanism shown in Scheme I, where substrate binds rapidly to only one of two conformers of the free enzyme and interconversion between conformers is slow.…”
Section: Resultsmentioning
confidence: 99%